Blade runner - The Final Cut - Deeley, Michael; Fancher, Hampton; Peoples, David Webb.; Scott, Ridley; Ford, Harrison, 1942-; Hauer, Rutger, 1944-; Young, Sean.; Olmos, Edward James; Hannah, Daryl; Cronenweth, Jordan; Rawlings, Terry; Vangelis; et al. (Burbank, CA : Warner Home Video, 2007)
Rick Deckard prowls the steel-and-microchip jungle of 21st -century Los Angeles. He's a "blade runner" stalking genetically-made criminal replicants. His assignment: kill them. Their crime: wanting to be human. This new version omits Deckard's voiceover narration, develops in slightly greater detail the romance between Deckard and Rachel, and removes the "uplifting" finale.
Originally released as motion picture in 2007
Based on the novel: Do androids dream of electric sheep / by Philip K. Dick.
Special features: scene access; cast biographies.
Director of photography, Jordan Cronoweth ; editor, Terry Rawlings ; music, Vangelis.
Harrison Ford, Rutger Hauer, Sean Young, Edward James Olmos, Daryl Hannah.
MPAA rating: R.
Keywords: Androids -- Drama; Twenty-first century -- Drama; Feature films; Science fiction films; Los Angeles (Calif.) -- Drama